IMPLEMENTASI ALGORITMA C5.0 PADA KELULUSAN PESERTA UJIAN KEMAHIRAN BERBAHASA INDONESIA (UKBI) PADA BALAI BAHASA SUMATERA UTARA - Mauhati Pardede; Efori Buulolo; Eferoni Ndruru (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The development of the modern era has made many people more influenced in using foreign languages in their daily lives. Almost every day, the people especially the generation in this era understand more about the use of foreign languages than the language from their own country. One of the efforts to strengthen the position of Indonesian is carried out by the Balai Balai Bahasa by developing an Indonesian language proficiency test tool called the Indonesian Language Proficiency Test (UKBI). The Indonesian Language Proficiency Test (UKBI) was assessed based on several factors of the participant's ability to listen, respond to the rules, read, write and speak. So far some of the UKBI participants at the North Sumatra Language Center have failed or failed, one of the contributing factors is that the assessment was not fulfilled. To overcome the problems above, a method is needed. The technique that can be utilized in the process of processing data is the classification with the C5.0 algorithm. C5.0 algorithm is a classification algorithm applied to decision tree techniques that are processed using information gain. In selecting attributes for object breakers in several classes, the attribute that produces the greatest information gain with the highest information gain value will be chosen as the parent of the next node.Keywords: Indonesian Language Proficiency Test, C5.0 Algorithm